Hepatology topics of special interest from Central Europe (Czech Republic, Hungary, Poland, Slovakia) - Hunyady, Bela; Jaroszewicz, Jerzy; Lipták, Ľubomír; Skladaný, Ľubomír; Sperl, Jan; Šváč, Juraj (Clinical and Experimental Hepatology, 2016)
This compilation represents abstracts of presentations at the first meeting of the Initiative Group for the Central European Hepatologic Collaboration (CEHC, Warsaw, 19-21 November, 2015) on topics with special interest from four Central European countries and includes a summary of a boceprevir-based triple therapy cohort programme (from Hungary), current trends and challenges in liver diseases (from Poland), acute kidney injury in liver cirrhosis (from Slovakia) and treatment of hepatitis C in haemodialysed patients (from the Czech Republic). All these topics are or have been of high interest during the last several years, and many of them are still not completely resolved with the emergence and availability of the novel interferon-free therapies for hepatitis C and with other advances in the pathophysiology and treatment of liver diseases.